Assessment of Population and ECM Production Using Multiphoton Microscopy as an Indicator of Cell Viability. - Vielreicher, Martin; Friedrich, Oliver (Methods in Molecular Biology, 2017)
Multiphoton microscopy allows continuous depth-resolved, nondestructive imaging of scaffold-seeded cells during cell or tissue culture. Spectrally separated images in high resolution can be provided while cells are conserved in their native state. Here we describe the seeding of mesenchymal stem cells to bacterial nanocellulose hydropolymer scaffolds followed by 2-channel imaging of cellular autofluorescence (AF) and collagen-I formation using second harmonic generation (SHG) signals. With this approach the simultaneous observation of the progression of cell morphology and production of extracellular matrix as hallmarks of viability and cell fitness is possible.